Peran Strategi Pembelajaran Humanistik dalam Meningkatkan Motivasi Belajar PAI Siswa - Pooja Firstisya; Novi Khayatul Jannah; Gusmaneli Gusmaneli (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research discusses the role of humanistic teaching strategies in enhancing students' learning motivation in Islamic Religious Education (PAI). Humanistic teaching strategies focus on the holistic development of students, addressing cognitive, emotional, and spiritual aspects. Through this approach, students are given opportunities to relate learning material to their personal experiences, which in turn increases their engagement and intrinsic motivation to learn. This research uses the library research method to collect and analyze various literatures related to humanistic teaching, learning motivation, and its implementation in PAI. The findings of this study indicate that the application of humanistic strategies in PAI teaching can create a more inclusive environment, improve positive interactions between teachers and students, and encourage students to learn more meaningfully and with greater motivation.